2017
DOI: 10.1542/peds.2016-2822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recruitment Strategy Outcomes in the National Children’s Study

Abstract: PBS demonstrated the optimal combination of recruitment success, efficiency, cost, and population representativeness and serves as a model for the assembly of future prospective probability-based birth cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It is therefore the ethical duty of research teams to design and execute clinical studies with past transgressions in mind, actively working to build trust while also avoiding potential for coercion [12]. Indeed, relationship building among research teams and potential participants has shown to be key to recruitment, including in perinatal research [13][14][15]. What remains less clear is how logistical aspects of the recruitment process affect enrollment of Black women into observational studies of perinatal biology.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore the ethical duty of research teams to design and execute clinical studies with past transgressions in mind, actively working to build trust while also avoiding potential for coercion [12]. Indeed, relationship building among research teams and potential participants has shown to be key to recruitment, including in perinatal research [13][14][15]. What remains less clear is how logistical aspects of the recruitment process affect enrollment of Black women into observational studies of perinatal biology.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers, 60 percent of whom have more than 10 years of scientific experience, range from undergraduate and graduate students to research scientists, professors and medical doctors. Over fifty peer reviewed publications have resulted from use of NCS Vanguard data and specimens ( 1 7 , 24 69 ) as of January 2021.…”
Section: Resultsmentioning
confidence: 99%
“…The ARS was followed in June 2012 by another substudy, the Provider-Based Sampling (PBS) Substudy, which was conducted in three study locations ( 6 ). Overall, the PBS strategy proved most effective and cost efficient ( 7 ). In December of 2014, the Vanguard Study was discontinued by the National Institutes of Health (NIH) Director following the recommendations of a National Children's Study Working Group ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent survey found that, generally, women are interested in participating in programs like Early Check [27], so a key activity has been testing and evaluating remote recruitment procedures to reach these women and their families. An analysis of outreach and recruitment approaches in the National Children’s Study found that there is no magic bullet for outreach and recruitment, and multiple strategies are required [28]. We designed a systematic, evidence-based, multiphase method approach for large-scale recruitment that excludes in-person recruitment (at least for the present time).…”
Section: Key Components Of Early Checkmentioning
confidence: 99%